Indoor Pollutants - National Research Council (The National Academies Press, 1981)
Keywords: Environment and Environmental Studies

U.S. Health in International Perspective: Shorter Lives, Poorer Health - Institute of Medicine; National Research Council (The National Academies Press, 2013)
The United States is among the wealthiest nations in the world, but it is far from the healthiest. Although life expectancy and survival rates in the United States have improved dramatically over the past century, Americans live shorter lives and experience more injuries and illnesses than people in other high-income countries. The U.S. health disadvantage cannot be attributed solely to the adverse health status of racial or ethnic minorities or poor people: even highly advantaged Americans are in worse health than their counterparts in other, "peer" countries. In light of the new and growing evidence about the U.S. health disadvantage, the National Institutes of Health asked the National Research Council (NRC) and the Institute of Medicine (IOM) to convene a panel of experts to study the issue. The Panel on Understanding Cross-National Health Differences Among High-Income Countries examined whether the U.S. health disadvantage exists across the life span, considered potential explanations, and assessed the larger implications of the findings. U.S. Health in International Perspective presents detailed evidence on the issue, explores the possible explanations for the shorter and less healthy lives of Americans than those of people in comparable countries, and recommends actions by both government and nongovernment agencies and organizations to address the U.S. health disadvantage.
Keywords: Behavioral and Social Sciences; Health and Medicine; Surveys and Statistics

Lessons Learned from Diverse Efforts to Change Social Norms and Opportunities and Strategies to Promote Behavior Change in Behavioral Health: Proceedings of Two Workshops - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
In 2015, the National Academies of Sciences, Engineering, and Medicine convened two workshops with oversight from the Committee on the Science of Changing Behavioral Health Social Norms. The workshops provided input to the committee's deliberations and contributed to the development of the report Ending Discrimination against People with Mental and Substance Use Disorders. That report was issued to help the Substance Abuse and Mental Health Services Administration and the Office of the Assistant Secretary for Planning and Evaluation, U.S. Department of Health and Human Services, utilize the scientific evidence base in improving public attitudes toward and understanding of behavioral health, specifically in the areas of mental health and substance use disorders. This publication summarizes the presentations and discussions at the two workshops.
Keywords: Behavioral and Social Sciences

The Potential Contribution of Cancer Genomics Information to Community Investigations of Unusual Patterns of Cancer: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Where people live can affect their health because of location-specific exposure to chemicals and toxicants, lifestyle, diet, immune function development, and social and historical determinants of health. A better understanding of the connections between environmental exposures and genetics that are associated with cancer can help inform efforts to identify risks and prevent potentially harmful outcomes. Recent scientific advancements have brought new insights into genomic and epigenomic biomarkers of cancer, which encompasses the toxicogenomic effects of environmental hazards, genetic susceptibility to environmental exposures, and the role of genetic and epigenetic changes in the development of cancer. Public communication around the potential risks of environmental hazards has also been evolving. The National Academies of Sciences, Engineering, and Medicine National Cancer Policy Forum convened a virtual public workshop in collaboration with the Roundtable on Genomics and Precision Health on April 13, 2023 to explore the state of the science in identifying potential genomic and epigenomic biomarkers of environmental exposures associated with cancers, with an emphasis on pediatric cancers. This proceedings document summarizes workshop discussions.
Keywords: Health and Medicine

Informing the Future: Critical Issues in Health: Fourth Edition - Institute of Medicine (The National Academies Press, 2007)
Keywords: Health and Medicine

Metrics That Matter for Population Health Action: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In times of rapid change and constrained resources, measures that are important, focused, and reliable are vital. However there is an overabundance of measures available for evaluating various aspects of population health and previous efforts to simplify existing sets to meet the needs of all decision makers have been unsuccessful. The National Academies of Sciences, Engineering, and Medicine convened a workshop to explore the status and uses of measures and measurement in the work of improving population health. Participants explored existing and emerging population health metric sets and characteristics of metrics necessary for stakeholder action across multiple sectors. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Childhood Obesity Prevention in Texas: Workshop Summary - Institute of Medicine (The National Academies Press, 2009)
Childhood Obesity Prevention in Texas summarizes the information gathered at a workshop held February 5-6, 2009, in Austin, Texas. At this workshop, committee members met with Texas lawmakers, public officials, and community leaders to exchange ideas and to view first-hand strategies that are being implemented effectively at the state and local levels to prevent and reverse childhood obesity.
Keywords: Health and Medicine; Food and Nutrition

Public Information and Education in the Promotion of Highway Safety - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2007)
TRB's National Cooperative Highway Research Program (NCHRP) Research Results Digest 322: Public Information and Education in the Promotion of Highway Safety assesses the role of public information and education programs in contributing to behavior change in the highway safety area.
Keywords: Transportation and Infrastructure

Measuring the Risks and Causes of Premature Death: Summary of Workshops - Institute of Medicine; National Research Council (The National Academies Press, 2015)
Measuring the Risks and Causes of Premature Death is the summary of two workshops conducted by The Committee on Population of the National Research Council at the National Academies to address the data sources, science and future research needs to understand the causes of premature mortality in the United States. The workshops reviewed previous work in the field in light of new data generated as part of the work of the NRC Panel on Understanding Divergent Trends in Longevity in High-Income Countries (NRC, 2011) and the NRC/IOM Panel on Understanding Cross-National Differences Among High-Income Countries (NRC/IOM, 2013). The workshop presentations considered the state of the science of measuring the determinants of the causes of premature death, assessed the availability and quality of data sources, and charted future courses of action to improve the understanding of the causes of premature death. Presenters shared their approaches to and results of measuring premature mortality and specific risk factors, with a particular focus on those factors most amenable to improvement through public health policy. This report summarizes the presentations and discussion of both workshops.
Keywords: Behavioral and Social Sciences; Health and Medicine

A History of the National Academy of Medicine: 50 Years of Transformational Leadership - National Academy of Medicine (The National Academies Press, 2022)
Commissioned to mark the 50th anniversary of the National Academy of Medicine (NAM; formerly the Institute of Medicine [IOM]), this volume describes the circumstances that led to the IOM's founding in 1970, the members and leaders who built and sustained the organization, and the process by which the IOM became the NAM in 2015. The volume also details a selection of the IOM/NAM's most influential contributions to biomedical science, U.S. health care, and population health and concludes with the story of how the organization navigated unprecedented national and global crises between 2015 and 2021.
Keywords: Health and Medicine

Leading Health Indicators 2030: Advancing Health, Equity, and Well-Being - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Beginning in 1979 and in each subsequent decades, the U.S. Department of Health and Human Services (HHS) has overseen the Healthy People initiative to set national goals and objectives for health promotion and disease prevention. At the request of HHS, this study presents a slate of Leading Health Indicators (LHIs) that will serve as options for the Healthy People Federal Interagency Workgroup to consider as they develop the final criteria and set of LHIs for Healthy People 2030.
Keywords: Health and Medicine

Exploring Tax Policy to Advance Population Health, Health Equity, and Economic Prosperity: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine's Roundtable on Population Health Improvement has been focused on the subject of dependable resources for population health since its inception in 2013. On December 7, 2017, the roundtable convened a workshop to explore tax policy as it relates to advancing population health, health equity, and economic prosperity. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Asbestos: Selected Cancers - Institute of Medicine (The National Academies Press, 2006)
In conjunction with drafting comprehensive legislation concerning compensation for health effects related to asbestos exposure (the Fairness in Asbestos Injury Act), the Senate Committee on the Judiciary directed the Institute of Medicine to assemble the Committee on Asbestos: Selected Health Effects. This committee was charged with addressing whether asbestos exposure is causally related to adverse health consequences in addition to asbestosis, mesothelioma, and lung cancer. Asbestos: Selected Cancers presents the committee&#39s comprehensive distillation of the peer-reviewed scientific and medical literature regarding association between asbestos and colorectal, laryngeal, esophageal, pharyngeal, and stomach cancers.
Keywords: Health and Medicine; Environment and Environmental Studies

Marking, Rendering Inert, and Licensing of Explosive Materials: Interim Report - National Research Council (The National Academies Press, 1997)
Keywords: Conflict and Security Issues

Dispelling the Myths About Addiction: Strategies to Increase Understanding and Strengthen Research - Institute of Medicine (The National Academies Press, 1997)
Every year about half a million men, women, and children in the United States die from the effects of using nicotine, alcohol, and illegal drugs: one of every four American deaths. Yet research to solve this terrible problem is often perceived as less important than other types of biomedical investigation. Focusing on four major classes of drugs with the greatest social and economic impact—nicotine, alcohol, opioids, and stimulants—Dispelling the Myths About Addiction examines what is known about addiction and what is needed to develop a talented cadre of investigators and to educate the public about addiction research. The committee explores these areas:
Keywords: Health and Medicine

The Current State of Obesity Solutions in the United States: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
For the first time in decades, promising news has emerged regarding efforts to curb the obesity crisis in the United States. Obesity rates have fallen among low-income children in 18 states, the prevalence of obesity has plateaued among girls, regardless of ethnicity, and targeted efforts in states such as Massachusetts have demonstrably reduced the prevalence of obesity among children. Although the reasons for this turnaround are as complex and multifaceted as the reasons for the dramatic rise in obesity rates in recent decades, interventions to improve nutrition and increase physical activity are almost certainly major contributors. Yet major problems remain. Diseases associated with obesity continue to incur substantial costs and cause widespread human suffering. Moreover, substantial disparities in obesity rates exist among population groups, and in some cases these disparities are widening. Some groups and regions are continuing to experience increases in obesity rates, and the prevalence of severe obesity is continuing to rise. The Current State of Obesity Solutions in the United States is the summary of a workshop convened in January 2014 by the Institute of Medicine Roundtable on Obesity Solutions to foster an ongoing dialogue on critical and emerging implementation, policy, and research issues to accelerate progress in obesity prevention and care. Representatives of public health, health care, government, the food industry, education, philanthropy, the nonprofit sector, and academia met to discuss interventions designed to prevent and treat obesity. The workshop focused on early care and education, schools, worksites, health care institutions, communities and states, the federal government, and business and industry. For each of these groups, this report provides an overview of current efforts to improve nutrition, increase physical activity, and reduce disparities among populations.
Keywords: Food and Nutrition; Health and Medicine

Cotton Boll Weevil: An Evaluation of USDA Programs : a Report - National Research Council (The National Academies Press, 1981)
Keywords: Agriculture

Capturing Social and Behavioral Domains and Measures in Electronic Health Records: Phase 2 - Institute of Medicine (The National Academies Press, 2014)
Determinants of health - like physical activity levels and living conditions - have traditionally been the concern of public health and have not been linked closely to clinical practice. However, if standardized social and behavioral data can be incorporated into patient electronic health records (EHRs), those data can provide crucial information about factors that influence health and the effectiveness of treatment. Such information is useful for diagnosis, treatment choices, policy, health care system design, and innovations to improve health outcomes and reduce health care costs. Capturing Social and Behavioral Domains and Measures in Electronic Health Records: Phase 2 identifies domains and measures that capture the social determinants of health to inform the development of recommendations for the meaningful use of EHRs. This report is the second part of a two-part study. The Phase 1 report identified 17 domains for inclusion in EHRs. This report pinpoints 12 measures related to 11 of the initial domains and considers the implications of incorporating them into all EHRs. This book includes three chapters from the Phase 1 report in addition to the new Phase 2 material. Standardized use of EHRs that include social and behavioral domains could provide better patient care, improve population health, and enable more informative research. The recommendations of Capturing Social and Behavioral Domains and Measures in Electronic Health Records: Phase 2 will provide valuable information on which to base problem identification, clinical diagnoses, patient treatment, outcomes assessment, and population health measurement.
Keywords: Health and Medicine

Country-Level Decision Making for Control of Chronic Diseases: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
A 2010 IOM report, Promoting Cardiovascular Health in the Developing World, found that not only is it possible to reduce the burden of cardiovascular disease and related chronic diseases in developing countries, but also that such a reduction will be critical to achieving global health and development goals. As part a series of follow-up activities to the 2010 report, the IOM held a workshop that aimed to identify what is needed to create tools for country-led planning of effective, efficient, and equitable provision of chronic disease control programs.
Keywords: Health and Medicine

Bridging the Evidence Gap in Obesity Prevention: A Framework to Inform Decision Making - Institute of Medicine (The National Academies Press, 2010)
To battle the obesity epidemic in America, health care professionals and policymakers need relevant, useful data on the effectiveness of obesity prevention policies and programs. Bridging the Evidence Gap in Obesity Prevention identifies a new approach to decision making and research on obesity prevention to use a systems perspective to gain a broader understanding of the context of obesity and the many factors that influence it.
Keywords: Food and Nutrition; Health and Medicine